Load combination feedback of fracture in concrete dams based on monitoring data with simplified fuzzy association rules. (January 2023) - Qin, Xiangnan; Gu, Chongshi; Guo, Jinjun; Yuan, Dongyang; Shao, Chenfei; Chen, Xudong
Abstract: The existed cracks are serious potential threats to the integrity and safety of concrete dams, and may even lead to dam failure and flood disaster. The fracture behavior in concrete dams is influenced by a kaleidoscope of load effects, which act in combination with a complicated relationship. A quantitative analysis method with improved association rule mining (ARM) based on monitored crack opening is proposed in this study. Fuzzy Set theory and Fuzzy C-Means method are introduced to establish the fuzzy ARM method for sequential monitoring data, and the traditional Apriori algorithm is simplified based on the single decision attribute. The feasibility and efficiency of the proposed method is validated by its application in Chencun gravity arch dam with a large structural fracture, and low temperature and low upstream water level are identified as the detrimental load combination for propagation of the fracture in this dam.